Fight Fungi with Fungi: Antifungal Properties of the Amphibian Mycobiome - Kearns, Patrick J.; Fischer, Sarah; Fernández-Beaskoetxea, Saioa; Gabor, Caitlin R.; Bosch, Jaime; Bowen, Jennifer L.; Tlusty, Michael F.; Woodhams, Douglas C. (Frontiers in Microbiology, 2017)
Emerging infectious diseases caused by fungal taxa are increasing and are placing a substantial burden on economies and ecosystems worldwide. Of the emerging fungal diseases, chytridomycosis caused by the fungus Batrachochytrium dendrobatidis (hereafter Bd) is linked to global amphibian declines. Amphibians have innate immunity, as well as additional resistance through cutaneous microbial communities. Despite the targeting of bacteria as potential probiotics, the role of fungi in the protection against Bd infection in unknown. We used a four-part approach, including high-throughput sequencing of bacterial and fungal communities, cultivation of fungi, Bd challenge assays, and experimental additions of probiotic to Midwife Toads (Altyes obstetricans), to examine the overlapping roles of bacterial and fungal microbiota in pathogen defense in captive bred poison arrow frogs (Dendrobates sp.). Our results revealed that cutaneous fungal taxa differed from environmental microbiota across three species and a subspecies of Dendrobates spp. frogs. Cultivation of host-associated and environmental fungi realved numerous taxa with the ability to inhibit or facilitate the growth of Bd. The abundance of cutaneous fungi contributed more to Bd defense ( 45% of the fungal community), than did bacteria ( 10%) and frog species harbored distinct inhibitory communities that were distinct from the environment. Further, we demonstrated that a fungal probiotic therapy did not induce an endocrine-immune reaction, in contrast to bacterial probiotics that stressed amphibian hosts and suppressed antimicrobial peptide responses, limiting their long-term colonization potential. Our results suggest that probiotic strategies against amphibian fungal pathogens should, in addition to bacterial probiotics, focus on host-associated and environmental fungi such as Penicillium and members of the families Chaetomiaceae and Lasiosphaeriaceae.